2021
DOI: 10.3390/jcm10153416
|View full text |Cite
|
Sign up to set email alerts
|

Change in Shoulder Function in the Early Recovery Phase after Breast Cancer Surgery: A Prospective Observational Study

Abstract: Breast cancer surgery significantly affects the shoulder’s range of motion (ROM) and strength. However, the extent of shoulder impairment, as well as patterns of recovery immediately after surgery, is not fully understood. Therefore, we aimed to investigate shoulder ROM and strength during the early recovery phase after surgery. Thirty-two breast cancer patients were observed five times: the day before surgery, discharge day (postoperative day 1 (POD1) or (POD2)), first outpatient visit (POD7–10), second outpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
1
11
0
3
Order By: Relevance
“…According to other studies on shoulder morbidity after mastectomy, shoulder ROM decreases until the first postoperative month and shows gradual improvement until postoperative month 12, when it reaches a plateau. [25][26][27][28] Even though our study focused on the shoulder ROM change after tissue expander-to-implant exchange surgery, not mastectomy, the postoperative shoulder ROM progress in our study is similar to that of other studies, as shown in ►Fig. 4.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…According to other studies on shoulder morbidity after mastectomy, shoulder ROM decreases until the first postoperative month and shows gradual improvement until postoperative month 12, when it reaches a plateau. [25][26][27][28] Even though our study focused on the shoulder ROM change after tissue expander-to-implant exchange surgery, not mastectomy, the postoperative shoulder ROM progress in our study is similar to that of other studies, as shown in ►Fig. 4.…”
Section: Discussionsupporting
confidence: 83%
“…It seems essential to improve patients' shoulder movement to increase the return-to-work rate and quality of life. 25 26 27 Patients who undergo both subpectoral reconstruction and PMRT are more prone to severe shoulder morbidities, which decrease their quality of life. 8 More delicate management is needed to reduce shoulder discomfort, particularly in irradiated patients who undergo subpectoral reconstruction after mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…When shoulder recovery patterns were analyzed by the number of lymph nodes removed, recovery patterns did not differ by the number of lymph nodes. 73 This may suggest that arm positioning during the surgery may have an important role in determining the impact on ROM.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, shoulder Range of Motion (ROM) on the unaffected side also experiences a decrease [22]. Clinically, patients commonly present with shoulder pain and limited ROM, typically manifesting as reduced abduction and internal rotation during both active and passive movements [23,24]. Frozen shoulder is often accompanied by pain, and previous reports indicate that levels of pain and dysfunction correlate with altered kinematics (25).…”
Section: Breast Cancer and The Associated Complications Following Bre...mentioning
confidence: 99%